Bridging the Gap of Ineffective Coordination in Indonesia: A Comparative Study on the Functional Differentiation and Dominus Litis Principle - Nelson, Febby Mutiara; Aini, Abni Nur (Media Iuris, 2025)
The ongoing reform of the Indonesian Criminal Procedure Code (“KUHAP”) seeks to align with the new Criminal Code (“KUHP 1 Tahun 2023”), which will take effect in 2026. A central issue in this reform concerns the coordination mechanism between investigators and public prosecutors, particularly the tension between functional differentiation and the principle of dominus litis. While functional differentiation separates the roles of investigators and prosecutors, dominus litis positions the prosecutor as the main authority responsible for controlling the progress of criminal cases. This study employs doctrinal legal research combined with a comparative approach to examine coordination practices in the Netherlands, France, China, and Thailand. The findings reveal that functional differentiation under the 1981 KUHAP limits the prosecutor’s role as dominus litis (from the Latin term meaning “controller of the case”), resulting in disharmony in coordination between investigators and prosecutors. This lack of harmony leads to inefficiencies in the pre-prosecution process, including the recurring exchange of case files (bolak-balik perkara). In contrast, universal practice shows that early prosecutorial involvement during the investigation stage fosters mutual understanding and ensures accurate supervision, thereby minimizing procedural delays.Furthermore, by referring to Article 132 of the 2023 Criminal Code, this paper argues that the principle of functional differentiation should no longer apply in Indonesia. The new provision strengthens the prosecutor’s role as dominus litis, affirming that investigation is an inseparable part of prosecution.